Sputnik V vaccine elicits seroconversion and neutralizing capacity to SARS-CoV-2 after a single dose - Rossi, Andrés Hugo (2021)
Massive vaccination offers great promise for halting the global COVID-19 pandemic. However, the limited supply and uneven vaccine distribution create an urgent need to optimize vaccination strategies. We evaluate SARS-CoV-2-specific antibody responses after Sputnik V vaccination of healthcare workers in Argentina, measuring IgG anti-spike titers and neutralizing capacity after one and two doses in a cohort of naive or previously infected volunteers. By 21 days after receiving the first dose of the vaccine, 94% of naive participants develop spike-specific IgG antibodies. A single Sputnik V dose elicits higher antibody levels and virus-neutralizing capacity in previously infected individuals than in naive ones receiving the full two-dose schedule. The high seroconversion rate after a single dose in naive participants suggests a benefit of delaying administration of the second dose to increase the number of people vaccinated. The data presented provide information for guiding public health decisions in light of the current global health emergency.